Scientometric insights into dynamic capabilities: measuring academic impact and trends - Martínez-Pinzón, Cesar Anibal; Duque-Hurtado, Pedro Luis (Clío América, 2024)
The business world is characterized by the rapid pace of changes in technological, political, and economic spheres. It is important to have the theoretical foundations that allow for the management of these rapid changes on a global scale. Dynamic Capabilities (DC) is a theoretical framework that facilitates addressing this issue. The objective of this article is to highlight advances in the measurement of dynamic capabilities by replicating a previous study and using scientometric techniques. Searches were conducted in Scopus and Web of Science, and the data were analyzed from two perspectives: a scientometric approach and the Tree of Science algorithm. The results revealed a 17.39 % increase in scientific production between 2000 and 2022, identifying three main trends: "Dynamic Capabilities: Driving Performance and Innovation in Rapidly Evolving Technological Landscapes"; "Strategic Advantages of Supply Chain Dynamic Capabilities in Enhancing Competitiveness"; and "Emphasizing Digitalization: The Impact of Big Data on Promoting Flexibility and Organizational Learning." These findings significantly contribute to the understanding of dynamic capabilities in current business management and provide guidance for future research in this field